2020
DOI: 10.1148/radiol.2019190794
|View full text |Cite
|
Sign up to set email alerts
|

Initial M Staging of Rectal Cancer: FDG PET/MRI with a Hepatocyte-specific Contrast Agent versus Contrast-enhanced CT

Abstract: Background:The performance of PET/MRI in the determination of distant metastases (M stage) in rectal cancer relative to the current practice with contrast material-enhanced CT is largely unknown. Purpose:To compare the staging of clinical M stage rectal cancer with fluorine 18 fluorodeoxyglucose (FDG) PET/MRI (including dedicated liver and rectal MRI) to that of chest and abdominopelvic CT and dedicated rectal MRI. Materials and Methods:From January 2016 to August 2017, patients with newly diagnosed advanced m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 29 publications
0
23
0
1
Order By: Relevance
“…Furthermore, the high sensitivity and specificity of PET/MRI for determination of the M state in malignant diseases as compared with those of other diagnostics had been proven throughout the last years [8,26]. A study by Queiroz et al showed the high accuracy of PET/MRI in detection of metastatic disease in initial staging of rectal cancer, whereas sensitivity and specificity were even higher in a study by Yoon et al using a hepatocyte-specific contrast agent [6,27].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, the high sensitivity and specificity of PET/MRI for determination of the M state in malignant diseases as compared with those of other diagnostics had been proven throughout the last years [8,26]. A study by Queiroz et al showed the high accuracy of PET/MRI in detection of metastatic disease in initial staging of rectal cancer, whereas sensitivity and specificity were even higher in a study by Yoon et al using a hepatocyte-specific contrast agent [6,27].…”
Section: Discussionmentioning
confidence: 99%
“…Further deterministic sensitivity analysis showed good reliability of the results regarding other input parameters, variation of costs, sensitivity, and specificity of SCI and 18 F FDG PET/MRI, as well as the probability of occurrence of metastases in a wide range still leads to the cost-effectiveness of 18 F FDG PET/MRI over that of SCI. Additionally, the sensitivity and specificity of MRI in this study are based on examinations using a hepatocyte-specific contrast agent, resulting in higher sensitivity for MRI regarding hepatic metastases, which are common in rectal cancer [6]. Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Yoon et al [26] studied the diagnostic yield of FDG PET/ MRI for the purpose of M staging in a pool of 71 patients with newly diagnosed advanced mid-to-low rectal cancer. The [18F]FDG PET/MRI examination included additional dedicated MRI sequences of the liver (without and with gadoxetic acid) and the rectum.…”
Section: Resultsmentioning
confidence: 99%